Perioperative Antibiotic Use in Sleep Surgery: Clinical Relevance. (May 2022) - Abdelwahab, Mohamed; Marques, Sandro; Previdelli, Isolde; Capasso, Robson
Objective: Upper airway surgery is a common therapeutic approach recommended for patients with obstructive sleep apnea (OSA) to decrease disease burden. We aimed to evaluate the effect of perioperative antibiotic prescription on complication rates. Study Design: Retrospective cohort (national database). Setting: Tertiary referral center. Methods: This is a retrospective study of a large national health care insurance database (Truven MarketScan) from 2007 to 2015. Subjects diagnosed with OSA who had uvulopalatopharyngoplasty (UPPP) were included and stratified in single versus multilevel surgery. Other variables included smoking, age, sex, antibiotic prescription, and comorbidities based on the Elixhauser index. Evaluated outcomes were postoperative bleeding, intubation, pneumonia, superficial surgical site infection, tracheostomy, and hospital readmission. A multivariate regression model was created to assess each complication. Results: A total of 5, 798, 528 subjects received a diagnosis of OSA, of which 39, 916 were >18 years old and underwent UPPP, either alone or with additional procedures. The mean age was 43 years, and 73.4% were male. Antibiotic prescription was associated with less bleeding in UPPP alone, UPPP with nasal surgery, and UPPP with nasal and tongue surgery ( P < .001, P < .001, and P = .006, respectively). It was also associated with a lower prevalence of surgical site infection, pneumonia, tracheostomy, intubation, and hospital readmission ( P < .001). On a multivariate model, antibiotic prescription was significantly associated with a decreased rate of complications. Conclusions: Although former studies recommended against the use of antibiotics after tonsillectomy, our results suggest that antibiotic prescription after UPPP for OSA was associated with less bleeding, surgical site infection, pneumonia, intubation, tracheostomy, and hospital readmission 30 days postoperatively.